No girls allowed?: Fluctuating boundaries between gay men and straight women in gay public space. (December 2019) - Baldor, Tyler
How are boundaries between sexual identities constructed and maintained through interaction? I draw on ethnographic observation in Philadelphia gay bars popular among heterosexual patrons and supplemental interviews with young gay-identifying club-goers to illuminate how men make situational claims to gay space by drawing distinctions between who 'belongs' in gay bars and who does not through interaction. Conceptualizing gay space as a collectively accomplished 'mesh' of particular interaction rituals, I find that men activated membership boundaries when presumably straight women's nightlife rituals were perceived to threaten the continued production of gay space by 'straightening' it. Men did not enact boundaries when straight women energized men's rituals with positive emotional energy and contributed to a bar's collective 'gay' feeling. Broadly, these findings suggest that the generation of shared emotions across groups in spaces with contested meaning or function helps determine the salience of boundaries.